MODERN INFORMATION TECHNOLOGIES IN THE FIELD OF INSURANCE SERVICES - SYDORCHUK, Ivanna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
As a result of the research, conclusions were obtained regarding the economic essence of the concepts of "internet insurance" and "digital insurance". The advantages and disadvantages of insurance digitalization are identified. The main factors influencing the development of information technologies in the field of insurance services are considered. Foreign experience in implementing IT innovations in the insurance industry and the main promising trends for insurance in Ukraine were studied.Currently, the Ukrainian insurance market is focused on the maximum transition to online. However, global digitalization has not bypassed the insurance sector, and in 2024, InsurTech became one of the most actively developing sectors of the digital economy. Despite the fact that the insurance sector lags behind the banking industry in technological terms, it is in a unique position that allows it to experience all the benefits of Blockchain.Since the implementation of digital technologies in Ukraine has its own characteristics, and the range of InsurTech projects is not very large today, in the context of digitalization, the main promising trends for the insurance sector in Ukraine will be: the use of artificial intelligence and machine learning for more effective customer segmentation; transformation of insurance products into the format of electronic policies; use of mobile applications; Blockchain technologies for data management, which will help ensure data security and minimize fraud risks, as well as turn the insurance company's website into a tool for communications and sales; development of cooperation between insurance companies and InsurTech startups; the use of platforms to optimize business processes.
Keywords: internet insurance; digital insurance; IT innovations; information technology